ABO Blood Grouping in Partial and Complete Hydatidiform Molar Pregnancy - Afsheen Abro, Rubina Ahmedani, Saima Naz Shaikh, Shehmeen Khan, Urooj Bhatti, Andleeb Mumtaz Sodhar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The present study was conducted to analyze the correlation of ABO blood groups in pregnant mother’s suffering from partial and complete Hydatidiform mole (HM) reporting at our tertiary care hospital. Study Design: Observational study Place and Duration: Liaquat University Hospital, Hyderabad/Jamshoro from May 2018 to October 2018. Methods: The present observational study analyzed the ABO blood groups of diagnosed cases of partial and complete type HM reporting at the Department of Obstetrics and Gynecology. A sample of 100 pregnant women suffering from Partial and complete HM and of their husbands was studied by inclusion criteria. ABO blood groups of these patients were determined as A, B, AB and O groups. Blood samples were processed for complete blood counts. Tests were performed at the Diagnostic and Research Laboratory, Liaquat University Hospital Hyderabad by forward and reverse ABO blood typing. Severity of GTD was assessed by WHO index score. Statistical comparisons of continuous and categorical variables run on SPSS ver. 21.0 at 95% confidence interval (P≤0.05). Results: Clinical presenting features bleeding PV, pain, hyperemesis gravidarum, grape like vesicles passage PV, no fetal heart sound, ovarian enlargement and hyperthyroidism. Partial and complete Hydatidiform mole was common in blood group A noted in 53 and 13 respectively. While Partial and complete Hydatidiform mole in blood group O was noted in 20 and 8 patients respectively (P=0.0001). The β–hCG ranged from 50,000 to 10, 00,000 mIU/mL. Conclusion: It is concluded, the hydatidiform mole proves strong association with blood groups A and O. Pregnant women complaining of bleeding PV, hyperemesis gravidarum, grape like vesicles passage with blood group A and O should be thoroughly investigated to minimize the maternal health risk.